A cultura na escola ou escolarização da cultura?: um olhar sobre as práticas culturais dos índios Xacriabá - Veronica Mendes Pereira (2003)
The research here presented was developed between 2001 and 2003 in Caatinguinha, one of 29 tribes from the Indian territory of Xacriabá. Its objective was understanding the meanings, for these Indians, of their daily practices and describing them in their production contexts, identifying the learning processes included there. It starts from the notion of culture, expressed in official documents which base a distinguished Indian education to get to the cultural practices as a focus of investigation. The closely analyzed cultural practice was the one known as casas pintadas de toá. This practice is developed by some of the women from the tribe, who prepare and paint (with their image repertoire) the inside and outside walls of their houses with mineral paints and a mud called toá. The houses are painted every year, once, with the rain, the paintings dissolve. The reference for the methodology were ethnography principles and the development was done through the participant observation on the Caatinguinha tribe and though semi-structured interviews. From the analysis of the childrens daily life context it was possible to notice their unique learning experiences and then reflect upon the implications of different learning processes which help thinking about the relation between education and culture.